Association of dietary patterns with metabolic syndrome components in low-income, free-living Brazilian adults - Marsola, Fabiana Castillo [UNESP]; Rinaldi, Ana Elisa [UNESP]; Siqueira, Muriel [UNESP]; McLellan, Kátia Cristina Portero [UNESP]; Corrente, José Eduardo; Burini, Roberto Carlos [UNESP] (My University, 2011)
This study investigated the association of dietary patterns with sociodemographic markers and components of metabolic syndrome in free-living adults. A descriptive, cross-sectional study was done with a sample of 237 individuals registered at one Family Health Strategy Unit. Biochemical, clinical, socioeconomic and dietary data were collected. Multiple and logistic linear regression were used and the significance level was set at 5%. Three dietary patterns were found and named western pattern, healthy pattern and traditional pattern upon recommendations found in the literature. People with the traditional dietary pattern were older, those with the western dietary pattern had higher education levels and those with the healthy pattern had the lowest income in minimum wages. The healthy pattern presented the lowest odds ratio for abdominal obesity (0.60; CI: 0.44-0.82; p<0.05). High blood glucose was positively associated with the western pattern. The odds ratio for hypertriglyceridemia was highest for those in the highest quartile of processed food intake. The Western dietary pattern and high percentage of processed foods in the diet must be avoided if hyperglycemia and hypertriglyceridemia are to be prevented or treated; in analogy, the healthy pattern must be promoted to reduce the risk of abdominal obesity.
Keywords: Nutrition; Metabolic syndrome; Diet pattern; Low-income